How Much Do Patients Really Want to Know and how much they get about Medication adverse Effects from the Family physician? - Zelko, Erika; Cvek, Nina (Anali PAZU, 2022)
Advances in medicine and general social development have an impact on extending life expectancy. Consequently, this also translates into an increase in the number of patients with chronic diseases, leading to an increase in the number of prescribed medications. The success of treatment depends largely on the patient’s adherence to medication. The purpose of the study was to determine how much information about medicines patients want and how much they get from physicians. We conducted a cross-sectional survey. 528 patients (238 male and 290 female) completed a validated questionnaire and submitted it to a nurse in 51 family medicine clinics across Slovenia between June 2017 and January 2018. We distributed 1020 questionnaires; the response rate was 53.7%. The analysis included 238 (45.1%) males and 290 (54.9%) females. 53.8 % of the patients were always informed about the adverse effects of medications by their family physician (FP). 79.7% of patients want to hear information about their side effects from their FP. 42% of respondents want to hear all the side effects of medicines, no matter how rare they are. Elderly participants want to get statistically significant more information about the side effects of drugs (p = 0.001). In the 65+ age group, 54.1% of patients expressed an interest in being informed by their physician of all the side effects of medicines, while in the youngest 18-35 age group the interest was much lower (29.9%). We found that more than half of responders wanted to discuss the adverse effects with their FP. Due to fear of adverse effects, as many as 31.5% of patients discontinue or do not take prescribed medication at all. Patients’ education and empowerment will need to receive more attention in the outpatient clinics of FPs in the future. Intensifying the collaboration with a clinical pharmacist may improve in the future the public’s awareness of the importance of knowing the adverse effects of medicines.
Keywords: adverse effects of medications; patients; amount of information’s; family medicine